2001
DOI: 10.1021/bp0001415
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Recombinant Green Fluorescent Protein Using Chromatofocusing with a pH Gradient Composed of Multiple Stepwise Fronts

Abstract: Green fluorescent protein (GFP), which fluoresces in the green region of the visible spectrum and is widely used as a reporter for gene expression and regulation, was overexpressed in the JM105 strain of Escherichia coli transformed with pBAD-GFP. A two-step chromatofocusing procedure was used to purify GFP starting from cell lysate, with each step employing a pH gradient extending from pH 5.5 to 4.0. The first chromatofocusing step was performed using a low-pressure column in which a retained stepwise pH fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…4) of these two purified preparations obtained under the conditions of crude:tert-butanol ratios of 1:1 and 1:2 showed that both preparations are comparable in levels of purity. The estimated molecular mass (SDS-PAGE) was found to be 27 000 Da which agreed well with the reported molecular mass of the protein [4]. Thus any of the two procedures utilizing the two cycles of TPP constitute a fairly simple and efficient purification process for GFP.…”
Section: Sodium Dodecyl Sulphate-polyacrylamide Gel Electrophoresis (supporting
confidence: 82%
See 1 more Smart Citation
“…4) of these two purified preparations obtained under the conditions of crude:tert-butanol ratios of 1:1 and 1:2 showed that both preparations are comparable in levels of purity. The estimated molecular mass (SDS-PAGE) was found to be 27 000 Da which agreed well with the reported molecular mass of the protein [4]. Thus any of the two procedures utilizing the two cycles of TPP constitute a fairly simple and efficient purification process for GFP.…”
Section: Sodium Dodecyl Sulphate-polyacrylamide Gel Electrophoresis (supporting
confidence: 82%
“…Yakhnin et al [3] described a four-step purification procedure with rather poor 36% yield. Narahari et al [4] used two chromatofocussing steps to obtain a 50-fold increase in purity with 60% recovery. Use of immobilized metal affinity chromatography by Li et al [5] is perhaps the most convenient procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Purification processes for GFP fusion proteins require multiple steps of chromatography or immunoaffinity separations [10][11][12][13][14][15][16]. Multi-step purification protocols involve the use of different techniques, including hydrophobic-interaction chromatography (HIC) [13], immobilized metal affinity chromatography (IMAC) [11], and aqueous two-phase extraction (ATPE) [12].…”
Section: Introductionmentioning
confidence: 99%
“…It includes tag-based protocols [8,9], which does not always allow the separation of improperly folded or cyclized GFP from the correctly folded form of this protein [10], size exclusion chromatography [11], chromatofocusing [12], organic extraction [11], etc. It includes tag-based protocols [8,9], which does not always allow the separation of improperly folded or cyclized GFP from the correctly folded form of this protein [10], size exclusion chromatography [11], chromatofocusing [12], organic extraction [11], etc.…”
Section: Introductionmentioning
confidence: 99%